Pengaruh Styrofoam Sebagai Bahan Tambah Campuran AC-BC Batu Sungai Tetean Kabupaten Mamasa - Desi Nurhayati Sampe; Alpius; Elizabeth (Paulus Civil Engineering Journal, 2022)
Tetean River is a river located in Mamasa Regency, West Sulawesi. In this study, one of the efforts to improve the quality of the AC-BC mixture so that the service life remains stable is by utilizing styrofoam as an additive in the asphalt mixture. Styrofoam is white cork or a type of foam that is often found around in the form of cork that supports electronic goods which has a high economic value because it can be recycled, cheap and practical. Styrofoam is flexible, difficult to decompose, resistant to acids and bases and salts. Styrofoam content used is 0%, 2%, 4%, 6%, and 8%, of the asphalt weight. With the aim of understanding the characteristics of the AC-BC mixture using Styrofoam waste added material, to obtain the marshall stability value of the remaining AC-BC mixture and to determine the effect of Styrofoam on the AC-BC mixture. The test carried out was the AC-BC mixture test using the Marshall method (SNI 06-2489-1991). From testing the characteristics of the AC-BC mixture with Styrofoam added 0% - 8%, using the Conventional Marshall test it has met the general specification standards of Bina Marga 2018 and the value of the remaining Marshall stability obtained using the Marshall Immersion test is 96.48%.